2020
DOI: 10.1155/2020/7310768
|View full text |Cite
|
Sign up to set email alerts
|

A Nomogram Based on a Three-Gene Signature Derived from AATF Coexpressed Genes Predicts Overall Survival of Hepatocellular Carcinoma Patients

Abstract: Background. Hepatocellular carcinoma (HCC) is a common cancer with an extremely high mortality rate. Therefore, there is an urgent need in screening key biomarkers of HCC to predict the prognosis and develop more individual treatments. Recently, AATF is reported to be an important factor contributing to HCC. Methods. We aimed to establish a gene signature to predict overall survival of HCC patients. Firstly, we examined the expression level of AATF in the Gene Expression Omnibus (GEO), the Cancer Genome Atlas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…COX regression and Kaplan-Meier analyses suggested an association between high SLC41A3 expression and poor OS and DSS in LIHC and KIRC. This result is consistent with our previous study that showed SLC41A3 is a prognostic factor in LIHC patients ( 43 ). Aberrant SLC41A3 expression may exert impact on cancer progression, in part, through influence on mechanisms that maintaining genome stability.…”
Section: Discussionsupporting
confidence: 94%
“…COX regression and Kaplan-Meier analyses suggested an association between high SLC41A3 expression and poor OS and DSS in LIHC and KIRC. This result is consistent with our previous study that showed SLC41A3 is a prognostic factor in LIHC patients ( 43 ). Aberrant SLC41A3 expression may exert impact on cancer progression, in part, through influence on mechanisms that maintaining genome stability.…”
Section: Discussionsupporting
confidence: 94%
“… 11 AATF expression is elevated in hepatocellular carcinoma and contributes to poor prognosis. 15 Our results showed that AATF was overexpressed in 48.6% bladder cancer tissues which positively associated with T stage. This was also supported by data from Oncomine showing AATF upregulation in BC tissues.…”
Section: Discussionmentioning
confidence: 51%
“…The prognostic module proposed in our analysis was composed of CDCA8, KIF20A, KIF2C and CEP55, all of which are often reported as being dysregulated in HCC tissues (27)(28)(29)(30). First, cell division cycle associated 8 (CDCA8) is regarded as a significant oncogene that is involved in the pathological development of various cancers, including HCC (27) and pancreatic ductal adenocarcinoma (31).…”
Section: Discussionmentioning
confidence: 99%